Strategi Promosi Untuk Meningkatkan Daya Saing UMKM Kedai Gading Serpong - Santi Rimadias; Milka Abigail Soetadi; Jonathan Jonathan; Kenny Wellianto; Muhammad A; Novaristo Novaristo; Celine Chow; Natasya Natasya (Lembaga Pengembangan Kinerja Dosen, 2024)
This community service aims to increase the competitiveness and visibility of Kedai Gading Serpong MSMEs through the creation of offline promotional media and the addition of locations on Google Maps. Within ± 2 months, the community service team provided promotional assistance in the form of banner redesign, menu creation, and location improvements on Google Maps. Through the planning, implementation, and evaluation stages, the program has succeeded in improving the professionalism and accessibility of store customers. As a result, the increase in visibility and attractiveness of the store can be seen through the installation of banners, menu posts, and the addition of locations on Google Maps. Kedai Gading Serpong positively welcomed this program, showing success in improving promotions and services. In conclusion, the combination of offline and digital promotion is effective in developing MSMEs in the era of fierce market competition.